Group of people including John Rorke, Mary (Rorke) Archibald and Ernestine (Forward) Pike - Rorke Family (1905)
John Rorke is in the back row, far right. Mary (Rorke) Archibald is in the second row, second from left. Ernestine (Forward) Pike is in the second row, fourth from left. Cataloguer's title. Ernestine (Forward) Pike (1887-1950), daughter of Ernest Edward Forward and Tryphena (Butt) Forward, was born at Carbonear on 24 April 1887. She married Arthur S. Pike at Carbonear on 25 September 1913 and had 3 sons: Ernest Fletcher Pike, Arthur Pike Jr. and Ralph Forward Pike. She died at Providence, Rhode Island on 22 March 1950. Mary (Rorke) Archibald (1888-1952), daughter of James and Mary (Wilcox) Rorke, was born in 1888 at Carbonear. She was sister of James and John Rorke of the firm John Rorke & Sons, Ltd. She married Henry ''Harry'' Archibald of Harbour Grace in 1909. She died in 1952. John Rorke (1885-1966), Mary's older brother, was born at Carbonear on 17 October 1885. He worked with the family company, John Rorke and Sons, Limited. He married Cornelia Tucker and had four children: John G.W. (1921-), Elizabeth (1922), Mary (1924), Richard (1933-). John died on 9 January 1966. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.